Consumer market segmentation for physiotherapy service in Malaysia using qualitative approach - Tan, Soon Shuen (2018)
Physiotherapy service has experienced an increase in demand over the past few years in Malaysia. With the offer of professional services and public awareness, physiotherapy has provided a practical and evidence based treatment to physical problems. In fact, physiotherapy service has been growing and reached high revenues in past few years, generated by hundreds of governments and private providers, especially in Klang Valley. Both big and smaller physiotherapy providers are competing to bring patients/consumers the best services. To win in this competitive race, providers must understand the patients/consumers preference. The objective of this management project is to examine consumer preferences based on physiotherapy services in private centers in the Klang Valley. This is to boost business information by understanding the motivation / needs / belief of the consumers. The insights came from questionnaire answered by 50 consumers from ApplePhysio. ApplePhysio is a very successful homegrown startup / entrepreneur company with less than 8 years history, providing physiotherapy services to thousands of consumers via several centers and hospitals in Klang Valley. The analysis conducted has segmented four major segments of consumer preferences for physiotherapy services. The proposed consumers’ psychographic profiles are - Fix When It’s Needed, Health and Healthier, Love Choices and Personalized for Me. Each segment has been assessed and recommendations have been made in terms of size, growth and initiatives, enabling ApplePhysio to target them more effectively.